Farmers’ Rice Yield in Fallow - T. Aman Rice - Fallow Cropping Pattern Due to Variability in Genotype And Management (Bangladesh Agronomy Journal, 2022)
Farmers’ existing rice production practices provide key indications of interventions for improving yield in their environments. This study aimed to explore those indications in the Fallow - T. Aman rice - Fallow cropping pattern (CP) under rainfed farming practiced by the farmers in Kapasia, Gazipur. Research method employed one-to-one and face-to face interview of 154 farmers practicing the CP. The average yield of T. Aman was estimated as 3.23 t ha-1, slightly below the national average yield of 3.93 t ha-1, in the range of 1.18 to 5.65 t ha-1. Variety was one of the two broad factors that determined the yield variation. The high yeld potential (HYP) category absolutely preferred the production aim, where Swarna-Ranjit (31.2% by farmer) and BRRI dhan49 (24.7% by farmer) were the dominated varieties where average yields were very close (3.51 and 3.36 t ha-1) for Swarna-Ranjit and BRRI dhan49, respectively). Management was the second factor determining the yield variation within varieties. While both the varieties received similar maximum yield (5.65 t ha-1), Swarna-Ranjit produced the minimum yield of 1.40 t ha-1 and BRRI dhan49 of 1.98 t ha-1. This study did not find a consistent pattern of response of the three measured management components - transplanting time, seedling age and seedling density to yield in either variety. The yield variance of BRRI dhan49 under three management components was higher compared to Swarna-Ranjit. Farmers practiced relatively a wide range of three management combinations to achieve high yield in Swarna-Ranjit, but a narrow range of the three management combinations for BRRI dhan49 to achieve the same level of yield. It is concluded that the variety-specific agronomic management to be the avenue for yield improvements in farmers’ fields.Bangladesh Agron. J. 2022, 25(1): 23-36